Audit Committee Independence and Financial Performance: A Quantitative Assessment of Private Limited Companies In Uganda - John, Rwakihembo; Kamukama, Nixon; Kijjambu, Nsambu Fredrick (American Journal of Finance, 2022)
Purpose: Correlation of the financial performance and audit committee independence of private limited companies is the grounds that the study sought to explore. Methodology: The questionnaire was used to gather measurable data by utilising a cross-sectional strategy from the 394 companies picked in central as well as Western Uganda. Two methodologies, correlation and regression tactics, were deployed to carry out analytical, empirical data processing. Findings: Nonetheless, the study did not find any connection between the financial performance and audit committee independence of private limited companies institutions in Uganda. Recommendation: The study therefore endorses a blended structure of directors not only in executive posts to constitute an auditing committee. Consequently, this would eradicate information asymmetry and ensure flawless monitoring of management.
Keywords: Audit committee Independence; Financial Performance; Uganda